2012
DOI: 10.1111/j.1529-8019.2012.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vascular lesions and their management in Indian setting

Abstract: Indian skin with its broad range of skin color and complexion differs in the presentation and management of cutaneous vascular lesions. Common congenital and acquired vascular lesions are discussed with respect to the epidemiology, clinical presentation, and management strategies in an Indian setting. An effort has been made to review Indian case reports and studies of cutaneous vascular lesions, potential possible modification in the conventional treatment considering resource constraints, cultural practices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
2
1
0
Order By: Relevance
“…Our observational study is in agreement with other studies reported in the literature (2,(4)(5)(6)(7)(8)(9)(10). In our study, the efficacy of propranolol gave very good results (35.7%) in five patients, good in six patients (42.8%), and mild results in the last three patients (21.4%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observational study is in agreement with other studies reported in the literature (2,(4)(5)(6)(7)(8)(9)(10). In our study, the efficacy of propranolol gave very good results (35.7%) in five patients, good in six patients (42.8%), and mild results in the last three patients (21.4%).…”
Section: Discussionsupporting
confidence: 93%
“…These data are in agreement with the literature . In a meta‐analysis including 35 studies involving 324 IH patients and 248 controls, the efficacy of propranolol is higher than other therapies, with strong evidence as a first line therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Pulmonary fibrosis is the most important dose-dependent complication of systemic bleomycin therapy but has not been reported after intralesional bleomycin injection, as the dosage used in sclerotherapy is much lower than those used in oncology. Chaudry et al performed pulmonary function tests and radiographs on 31 patients and did not observe pulmonary abnormalities in a mean follow-up of 3.2 years [29][30][31][32][33][34]. In the current study, the observed complications of treatment were ulceration in 30 patients (8.8%), scarring in 10 patients (2.9%), and subcutaneous atrophy in 7 patients (2%).…”
Section: Discussionmentioning
confidence: 45%